2016
DOI: 10.4238/gmr.15027923
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the correlation between the TNF-α308G/A polymorphism and polycystic ovary syndrome

Abstract: ABSTRACT. Previous studies have suggested that the tumor necrosis factor alpha (TNF-α) gene 308G/A polymorphism may be associated with polycystic ovary syndrome (PCOS) risk. However, this relationship is controversial. The present meta-analysis aimed to evaluate the correlation between the TNF-α 308G/A polymorphism and susceptibility to PCOS. A systematic electronic search of PubMed and Embase databases was conducted using specific inclusion criteria. Summary odds ratios (ORs) and 95% confidence intervals (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These genes are mainly related to the insulin signaling pathway and IR, chronic inflammation, reproductive hormone disorders, and biosynthesis of androgens; such as those encoding insulin (INS), INS receptor (INSR), INSR substrates (IRS), methylenetetrahydrofolate reductase (MTHFR), IL family members, TNF-a, toll-like receptor 2 (TLR2), fat mass and obesity-associated protein (FTO), paraoxonase 1 (PON1), calpain 10 (CAPN10), peroxisome proliferatoractivated receptor g (PPAR-g), FSH receptor (FSHR), LH/ choriogonadotropin receptor (LHCGR), LH-b, sex hormonebinding globulin (SHBG), androgen receptor, transforming growth factor b (TGF-b), fibrillin 3 (FBN3), and vitamin D receptor (VDR) (17,(33)(34)(35)(36)(37). Nevertheless, the vast majority of candidate gene variants associated with PCOS in previous studies have not been replicated, indicating the possibility of substantial genetic heterogeneity across various ethnic populations or different genetic architectures underlying specific PCOS phenotypes (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Genetics Of Polycystic Ovary Syndromementioning
confidence: 99%
“…These genes are mainly related to the insulin signaling pathway and IR, chronic inflammation, reproductive hormone disorders, and biosynthesis of androgens; such as those encoding insulin (INS), INS receptor (INSR), INSR substrates (IRS), methylenetetrahydrofolate reductase (MTHFR), IL family members, TNF-a, toll-like receptor 2 (TLR2), fat mass and obesity-associated protein (FTO), paraoxonase 1 (PON1), calpain 10 (CAPN10), peroxisome proliferatoractivated receptor g (PPAR-g), FSH receptor (FSHR), LH/ choriogonadotropin receptor (LHCGR), LH-b, sex hormonebinding globulin (SHBG), androgen receptor, transforming growth factor b (TGF-b), fibrillin 3 (FBN3), and vitamin D receptor (VDR) (17,(33)(34)(35)(36)(37). Nevertheless, the vast majority of candidate gene variants associated with PCOS in previous studies have not been replicated, indicating the possibility of substantial genetic heterogeneity across various ethnic populations or different genetic architectures underlying specific PCOS phenotypes (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Genetics Of Polycystic Ovary Syndromementioning
confidence: 99%
“…According to a meta‐analysis of PCOS studies, the risk of this disorder is not associated with the –1031 T/C, –308G/A, or –805C/T polymorphism of TNF 103 . Another study similarly reported that there is probably no association between PCOS susceptibility and the –308G/A sequence variation of TNF 104 …”
Section: Inflammationmentioning
confidence: 99%
“…103 Another study similarly reported that there is probably no association between PCOS susceptibility and the -308G/A sequence variation of TNF. 104…”
Section: Infl Ammationmentioning
confidence: 99%